The significance of utilizing 3D modeling to assess the impact of underground blasting on surface landslide stability - Ersoy, Hakan; Kanik, Mustafa (Elsevier, 2025)
This study aims to investigate the potential impact of controlled blasting during transmission tunnel excavation on surface stability using 2D and 3D limit equilibrium (LE) analysis, and to compare the consistency of results obtained from different stability analysis methods. In the analyses, the factor of safety (FoS) values decreased as the active loads increased. This reduction in post-blasting FoS values as a function of active loads demonstrates the sensitivity of slope stability to vibrations induced by controlled blasting. In this study, a detailed comparison was also made between 2D and 3D limit equilibrium analyses and the results obtained. While the general tendency for analyses performed on the same section is for the FoS value derived from 2D analyses to be lower, when the entire surface is considered, the FoS value derived from 3D analyses is 10 % lower. This is due to the fact that the analyses are repeated over the entire surface until the cross section giving the lowest FoS is found in the 3D analyses. Also, due to the blasting effect, slip surface locations remained constant in 2D analyses, whereas in the 3D surface safety maps the FoS values decreased at different rates in different areas. In addition, the 3D stability analyses showed that if an active load of more than 5 kg is used, the surface stability will be compromised, depending on the vibration, because of the FoS limits of 1.1 defined in the relevant national regulations. In consideration of the aforementioned particulars, it is important in such critical projects to produce surface safety maps using 3D analysis.
Keywords: Landslide; 3D analysis; Blasting; Stability; Tunnel; Surface safety map